2018
DOI: 10.3382/japr/pfx043
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiologic survey of infectious bursal disease viruses in broiler farms raised under different vaccination programs

Abstract: SUMMARYOver a span of nearly 4 yr, 246 bursal tissue samples were collected from Brazilian commercial broiler flocks (Gallus gallus) throughout the country and imprinted to sample collection cards (Flinders Technology Associates (FTA) cards). A total of 75 infectious bursal disease virus (IBDV) strains was successfully detected from the FTA card imprints and were submitted for further identification and molecular characterization. Nucleotide and predicted amino acid sequences of the IBDV surface protein VP2 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Virus identification is usually achievable by sampling, detecting, and sequencing the immunodominant region of the virus. Several studies have reported the evolution of IBDV in some geographical locations around the world with the emergence of an antigenic variant (20,21) and recombinant (22), reassortant (23,24), and distinct (25,26) strains of the virus. These isolated strains of IBDV with diverse antigenicity have made vaccination programmes against IBDV more complex due to vaccine failure.…”
Section: Introductionmentioning
confidence: 99%
“…Virus identification is usually achievable by sampling, detecting, and sequencing the immunodominant region of the virus. Several studies have reported the evolution of IBDV in some geographical locations around the world with the emergence of an antigenic variant (20,21) and recombinant (22), reassortant (23,24), and distinct (25,26) strains of the virus. These isolated strains of IBDV with diverse antigenicity have made vaccination programmes against IBDV more complex due to vaccine failure.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the histopathological scores between the two experiments, SPF vs commercial birds, showed that commercial birds exhibited more severe lesions in lymphoid follicles than SPF birds in final weeks of the trial. These findings are expected because, in addition to the effect of the vaccine stimulating seroconversion, there is also an ever-present field challenge from the birds' environment (MUNIZ et al, 2017). Generally, in both experiments, bursal lesions indicative of vaccine virus replication was slightly detected from day 14 to 28 onward, reaching a peak at 28 days, for both the s.c. or in ovo schedule.…”
Section: Discussionmentioning
confidence: 63%
“…Based on the degree of attenuation, these vaccines can be classified as mild, intermediate, intermediate plus or hot, which are the closest to field viruses (OIE, 2011). Nowadays, immune complex and vector vaccines, as well as conventional vaccines, are currently used in Brazil to control Gumboro disease (MUNIZ et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The sanitary checkpoint and the disinfection complex as a whole are in a non-working condition (Figure 1). Before installing the disinfectant complex, it is necessary to carry out a number of measures to improve the internal state of the sanitary checkpoint -clean the room from clutter (food, rubble, garbage), carry out repairs, insulate the wires [5][6][7].…”
Section: Methodsmentioning
confidence: 99%